Collective formal synthesis of (±)-rhynchophylline and homologues. Issue 68 (1st July 2016) - Xu, Jun; Shao, Li-Dong; Shi, Xin; Ren, Jian; Xia, Chengfeng; Zhao, Qin-Shi
Abstract : A collective formal synthesis approach to six bioactive oxindole alkaloids, including (±)-rhynchophylline and its five homologues, is completed in a highly efficient way. Abstract : A collective formal synthesis approach to bioactive oxindole alkaloids, including (±)-rhynchophylline, (±)-isorhynchophylline, (±)-mitraphylline, (±)-formosanine, (±)-isomitraphylline, and (±)-isoformosanine, is completed in a protecting-group free manner. Besides multigram-scaled operations, the notable feature of the synthesis is the application of two one-pot, sequential transformations. Namely, two key tetracyclic intermediates pyridinium salt9 and monoester14 were prepared by a one-pot N -alkylation/cross-dehydrogenative coupling sequence and a one-pot Michael/Karpocho sequence with minimal purification, respectively.